Are Intimate Small Concerts Worth it? - Immanuel Mellis (INSAM)
Developing multiple streams of income is an essential method for surviving as an artist, but what streams should an artist pull from? The awareness of one's resources and knowledge of how to use them is what makes or breaks a musician. Many musicians may have overlooked three key resources: House Concerts, Secret Concerts, and Listening Rooms – small intimate venues commonly overlooked. Are these venues worth performing at? Based on one’s character, financial needs, and current connections, each of the three venues may or may not be resourceful. This article provides the insight needed to make a decision as to which small intimate concerts (if any) are financially good for you.